(3YbO GdJLGQI GdGdcJQhfjIs - (3aGOj eMeO YeGO GdOjf(B, (3Jhcds ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2010)
(3JYQja GdJLGQI GdGdcJQhfjI h NUGFUgG, eRGjG h UhQ GdJLGQI GdGdcJQhfjI , CQcGf YbO GdJLGQI GdGdcJQhfjI , GdJhKjb h GdGKHGJ aj YbO GdJLGQI GdGdcJQhfjI , GdJMcje h aQV efGRYGJ YbO GdJLGQI GdGdcJQhfjI , eGgjI GdJMcje GdGdcJQhfj h eRGjGg , GHQGe GJaGb GdJMcje GdGdcJQhfj (B.s
(3eQGLY U(B.255s
Keywords: (3GdJLGQI GdGdcJQhfjIs; (3GdJMcje GdGdcJQhfjs; (3GdYbhO GdJLGQjs